La PME Et L’entrepreneuriat Font-Ils L’objet De Recherche Au Maroc? Une Étude Bibliographique - Taouab, Omar; Ahsina, Khalifa; lemqueddem, Hamid Ait (European Scientific Journal, ESJ, 2016)
The evaluation of the research in SMES and entrepreneurship has been the subject of several research works. These works have been made particularly in the anglo-saxon countries, Busenitz et al (2003), Meyer and al, (2014), Lasch and Yami (2008) in France and Sánchez and Gutiérrez (2011) in Spain. By contrast, no analysis of scientific journals in the field of entrepreneurship has yet been made in Morocco, from where, the desirability of this work, if only by a comparison of the results with the work already cited. This article has thus, for the purpose of presenting the results of a bibliographic study of 237 articles of the three major journals of Moroccan management on 2005-2013. The results suggest that the research in entrepreneurship is still low with a rate of 12% of the whole research in management. That the review of the Moroccan trade and management made more than 62% of this production volume, and the qualitative methodology is the most used.